Understanding Suffering - Smith, David H. (The Hastings Center report, 1992)
Book reviewed in this article: Suffering and the Beneficent Community: Beyond Libertarianism. By Erich H. Loewy. The Nature of Suffering and the Goals of Medicine. By Eric J. Cassell.